Propagating Design Updates to Structured Analysis Meshes. (November 2022) - Lecallard, Benoit; Tierney, Christopher M.; Robinson, Trevor T.; Armstrong, Cecil G.; Nolan, Declan C.; Sansom, Alex
Abstract: Generating structured meshes is often an expensive process, limiting the use of high-fidelity numerical simulation methods for design, especially when the design is not yet fixed and design updates are likely. For hexahedral meshes generated by decomposing a B-Rep model into regions for which simple meshing strategies are known, robustly propagating design modifications to the decomposed representation and subsequent mesh is very challenging. In this paper, an approach is presented to propagate parametric update and feature changes to structured meshes. Geometric and topological modifications on the design model are identified first, enabling the equivalent modifications to be identified on the decomposition of the design model. Virtual topology operations used to generate the initial decomposition are combined with the meshing constraints of individual sub-regions to update the decomposition and associated mesh locally. The approach is demonstrated for a number of design updates. Graphical abstract: Highlights: Design modifications are propagated to structured meshes obtained by decomposition. Virtual topology is used to decompose and mesh a CAD model. Design changes are identified from the B-Rep and linked to the decomposed model. Hexahedral meshing constraints are used to update the partitioning strategy. Only modified volume cells are automatically re-meshed.